Cardio-ankle vascular index (CAVI) as an indicator of arterial stiffness - Sun CK (Dove Medical Press, 2013)
Cheuk-Kwan Sun Department of Emergency Medicine, Department of Medical Education, E-Da Hospital, I-Shou University, Kaohsiung, Taiwan Abstract: Arterial stiffness has been identified as an independent predictor of prognostic outcomes for patients with cardiovascular disease. Although measurement of pulse wave velocity has been a widely accepted noninvasive approach to the assessment of arterial stiffness, its accuracy is hampered by changes in blood pressure. Taking the exponential relation between intravascular pressure and arterial diameter into consideration, a stiffness parameter can be obtained by plotting the natural logarithm of systolic–diastolic pressure ratio against the arterial wall extensibility. Cardio-ankle vascular index (CAVI), which is calculated based on the stiffness parameter thus obtained, is theoretically independent of changes in blood pressure. With this distinct advantage, CAVI has been widely applied clinically to assess arterial stiffness in subjects with known cardiovascular diseases including those with diagnosed atherosclerosis, coronary heart disease, and stroke as well as those at risk, including those with hypertension, diabetes, the elderly, and the obese. Because of its enhanced sensitivity, not only has the index been used to discern subtle changes in the disease process, it has also been utilized in studying normal individuals to assess their potential risks of developing cardiovascular diseases. The primary aims of assessing arterial stiffness using CAVI are not only to aid in early detection of arteriosclerosis to allow timely treatment and change in lifestyle, but also to quantitatively evaluate the progression of disease and the effectiveness of treatment. Despite its merit of being unaffected by blood pressure, discretion in data interpretation is suggested because an elevated CAVI represents not just vascular stiffness caused by pathological changes in the arterial wall, but can also be attributed to an increased vascular tone brought about by smooth muscle contraction. Moreover, certain patient populations, such as those with an ankle-brachial index < 0.9, may give falsely low CAVI and are suggested to be excluded from study. Keywords: cardio-ankle vascular index, stiffness parameter, cardiovascular disease, atherosclerosis, arteriosclerosis, pulse wave velocity